Case Report Recurrent Hemoptysis Post Re-Embolization in a 49 Year-Old Male with Post Tuberculosis Lung Disease (PTLD) and Bronchiectasis - Primaputri, Cindy Carrissa; Pratiwi, Suryanti Dwi; Aslam, Ahmad Bayhaqi Nasir (Universitaas Brawijaya, 2024)
Introduction: Hemoptysis is a symptom of lung disease, could be caused by lung infections, structural disorders of the lung, malignancy or disorders from outside of the lung. One of the pulmonary intervention for hemoptysis is embolization with a success rate > 70%, but the recurrence rate reaches 10-55%. The prognosis is poor depending on the amount of bleeding (untreated cases can have a mortality risk of over 50%), etiology and presence of recurrences. Case Illustration: A 49-year-old Male came to the policlinic with recurrent hemoptysis for a year. Non-smoker. History of Lung Tuberculosis (TB), completed treatment 15 years ago. Imaging result showed widening of the right subcostal artery, right posterior intercostal artery, bronchiectasis, active lung tuberculosis and left pulmonary emphysema. First embolization was done during Anti-Tuberculosis Drug (ATD) treatment for 6 months. Symptom of hemoptysis reappeared, then second embolization and fiber optic bronchoscopy (FOB) was performed. From the evaluation, he was diagnosed with infected bronchiectasis and PTLD, therefore given antibiotic medications for 2 weeks. Discussion: Embolization had been done twice in this case, no significant result. Based on literature, recurrent hemoptysis can still occur with a percentage about 10-55% after embolization and in this case, it might be caused by previous lung structural disorder and lung infections (Lung TB and Infected bronchiectasis). Conclusion: Although embolization has a success rate of > 70% for hemoptysis treatment, recurrence can still occur and highly dependent on the cause itself and patient's previous lung condition. Keywords: Hemoptysis, Embolization, Bronchiectasis, FOB, Lung TB, PTLD, ATD